Identifying the contingencies of self‐worth associated with eating disorder symptoms: The use of choice‐based conjoint analysis - Rieger, Elizabeth; Prasetya, Kevin; Christensen, Bruce K.; Shou, Yiyun (The International journal of eating disorders, 2021)
Objective Self‐worth contingent on shape/weight is a diagnostic criterion and key maintaining factor for eating disorders. However, the role of other contingencies of self‐worth (i.e., domains in which self‐worth is invested) is largely unknown. Moreover, research has relied on self‐ratings of contingency strength, which are subject to distortion through socially desirable responding and limited self‐awareness, and may have limitations in terms of ecological validity. To overcome these limitations, the present study investigated a broad range of contingencies of self‐worth in relation to eating disorder pathology and employed a choice‐based conjoint (CBC) approach for assessing these contingencies. Method Young women and men from the community (N = 428) completed a CBC task to assess the domains in which self‐worth is invested, the Eating Disorder Examination Questionnaire (EDE‐Q) to assess eating disorder symptomatology, and the Balanced Inventory of Desirable Responding to assess socially desirable responding. Results Beta regression analyses showed that CBC thinness and athletic competence predicted higher scores on all EDE‐Q scales. CBC muscularity and facial attractiveness predicted higher scores, while coping ability and quality of relationships predicted lower scores, on various aspects of eating disorder symptoms. CBC social acceptance predicted lower eating disorder symptoms in males only. Discussion The findings suggest that a broader range of contingencies of self‐worth beyond shape/weight are relevant to eating disorder pathology and should be considered as potential underlying mechanisms and treatment targets. In addition, this first use of the CBC method in eating disorder research provides initial support for its validity and utility.